Antiplasmodial activity of the ethanol extract of Dacryodes edulis leaf in Plasmodium berghei infected mice - Okwesileze, Chikezie N.; Akuodor, Godwin C.; Ofor, Casimir C.; Aja, Daniel O. J.; Ibiam, Gideon A.; Ilo, Cajetan E. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Malaria treatment in Africa is increasingly becoming difficult resulting from Plasmodium falciparum resistant to available antimalarial agents. Therefore, evaluating plants used in traditional medicines can lead to alternative treatment against malaria. Methods: This study evaluated the antiplasmodial activity of ethanol extract of Dacryodes edulis in chloroquine sensitive Plasmodium berghei NK65 strain in mice. The 4-day suppressive test, repository and curative effect against established rodent malaria infection models were assayed in this study. The oral acute toxicity test and phytochemical screening were also carried out on the ethanol leaf extract. Results: The ethanol leaf extract of Dacryodes edulis (D. edulis) at varying doses of 100 mg/kg, 200 mg/kg, 400 mg/kg significantly (p<0.05) exhibited dose-dependent decrease in parasitaemia at suppressive, repository and curative studies. Chloroquine 10 mg/kg significantly (p<0.05) decreased parasitaemia levels in the three models of malaria infections. The antiplasmodial activity of the leaf extract is comparable with the standard drug. The extract was found to be non-toxic acutely in mice. Conclusions: The findings show that D. edulis ethanol leaf extract demonstrated high antiplasmodial activity in a dose-dependent fashion. Thus, supporting claims of the plant traditional therapeutic importance for malaria treatment, and can be developed as an alternative therapy against the disease.